A clinicoepidemiological study of psychiatric co-morbidity in Hansen's Disease - Ritu Rani; Gita R Tegta; Ghanshyam K Verma; Dinesh D Sharma; Mudita Gupta; Ajeet Negi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Leprosy is a chronic disease caused by mycobacterium leprae. Chronicity of the disease leads to various psychiatric co-morbidities, which are often undiagnosed and untreated. The main objectives of this study were to evaluate the frequency and nature of psychiatric co-morbidity in patients of Hansen's disease. Materials and Methods: Seventy confirmed cases of Hansen's disease between the ages of 18 and 60 years attending the department of dermatology of Indira Gandhi Medical College and Hospital, Shimla were evaluated for various manifestations of Hansen's disease and screened for psychiatric co-morbidity using GHQ-12 and diagnosed using ICD-10 checklist. Severity of depression and anxiety was assessed with HAM-D and HAM-A scales, respectively. Results: The prevalence of psychiatric co-morbidity was found in 27.14% of enrolled patients. Depression was most prevalent in (20%) mental disorder; followed by anxiety disorder (7.14%). Moderate depressive episode was the commonest seen in 11.42% patients whereas 5.71% patients had mild depression. Generalized anxiety disorder was seen in 1.42% whereas 5.71% patients had mixed anxiety disorder. Patients with higher education status, positive family history of leprosy, lepromatous leprosy, and hand deformities were significantly associated with higher psychiatric co-morbidity. Conclusion: Patients suffering from Hansen's disease have significantly high prevalence of psychiatric co-morbidity complicating the Hansen's disease. High index of suspicion is required to diagnose and treat it.